The effectiveness of psychoeducation to increase knowledge and parenting practices in caregivers of children with autism (Dhaka University Journal of Biological Sciences, 2016)
An attempt was made to see the impact of psycho-education to increase knowledge and parenting practices in caregivers of children with autism. A total of 40 caregivers (20 in experimental group and 20 in control group) of children with autism participated in this study. Pre-post research design was used to assess the concept about autism and parenting practices of the participants. Caregivers of the experimental group received a psycho-educational session and the control group did not receive the psycho-education session. The psychoeducational program consisted of three sessions held during three weeks (two hours in each week). The results were discussed in terms of clinical significance. Compared with the control group, the experimental group showed improvement in parenting practices and knowledge about autism both immediately after intervention.Dhaka Univ. J. Biol. Sci. 25(2): 97-102, 2016 (July)